Antecedents of Consumer Materialism: An exploration in Sri Lankan Context - Malkanthie M.A.A (Kelaniya Journal of Management, 2019)
Materialism is becoming a major problem in the world. Materialistic consumers consume more and even unnecessary things. Overconsumption is one of the major threats to the future of human survival. Hence, the intention of this research is to determine the antecedents of materialism in Sri Lankan context. Through the Literature review, the antecedents of materialism were identified as; depression, anxiety, self- esteem, and stress. Positivist approach with deductive reasoning was used in this study. Individual adult person was taken as the unit of study of this research and this is a single cross -sectional study. Sample of 450 adults was selected according to judgmental sampling technique representing nine provinces in Sri Lanka. Structured questionnaire was used as the data collection tool. Structural Equation Modeling was used to analyze the data. Findings show that self-esteem, depression, and stress significantly affect materialism. Further, Self-esteem and depression negatively affect the materialism while “stress” positively affect the materialism. These findings are useful to Marketing Managers to develop more effective marketing strategies in terms of segmentation, strategic brand communication and promotion. By accurately segmenting based on the facet of materialism that is dominant in a specific consumer behavior context will lead to the development of brand communication that better addresses consumer concerns.